The Integration Model of the Creative Economy and the Halal Industry in Promoting the Local Economy in Pekalongan - Arfania Zuhru Fila (Presscience, 2026)
This study aims to analyze the integration model of the creative economy and the halal industry in driving local economic growth in Pekalongan. The main focus is to identify how the subsectors of batik, halal culinary, Muslim fashion, and halal tourism can collaborate under halal principles to enhance the competitiveness of MSMEs. Using a qualitative descriptive approach with a literature study method, the research utilizes secondary data from official BPS reports, government policy documents, academic articles, and previous studies related to the creative economy and halal industry. Data were analyzed through content analysis involving data reduction, categorization, and descriptive narration, supported by source triangulation to ensure validity between academic literature, policy, and real MSME conditions. The findings reveal that the integration of the creative economy and the halal industry positively impacts MSME competitiveness. Batik serves as a cultural identity and globally competitive product through eco-friendly innovation, halal-certified culinary expands domestic and international markets, Muslim fashion promotes modest fashion trends, and halal tourism generates a multiplier effect on local trade. However, challenges remain in limited capital, low halal certification literacy, and suboptimal digital adoption. This study recommends strengthening regional government facilitation, accelerating halal certification, and providing Islamic financial support for MSMEs. Collaboration among academia, entrepreneurs, and policymakers is crucial to strengthening Pekalongan’s branding as a halal creative city. The study contributes to the literature on creative economy–halal industry integration by offering an applicable model for inclusive and sustainable local economic development.